Radio Direction Finder pada HF Band sebagai Elemen dari Passive Radar - Rustamaji, Rustamaji; Sawitri, Kania; Fuady, Ghaniyman (Faculty of Engineering, Universitas Tanjungpura, 2019)
A Radio detection and ranging (radar) is used to detect and track objects in the air and on land, one type of the radar that is known is a passive radar. The radio direction finder (RDF) as an element of a passive radar is used to determine the direction angle, based on a radio waves that emitted by an object. The purpose of this study is to produce a RDF that works on HF bands as passive radar elements. In this study a RDF has been produced, which consists: a receive antenna in the form of a dipole Î»/8 and a yagi 5 elements with horizontal polarization, a tuning circuit, an AM signal detector, an audio amplifier, and equipped with a level signal display in the form of a S meter and a loudspeaker. The test results for outside and inside the room at a certain time, the RDF can detect the angle of direction of horizontal plane of an object or AM transmitter from 0Â° to 360Â° in the frequency range between 4.02 to 10.76 MHz. The results of detecting the angle of direction of an object or a transmitting radio waves in the HF band, in the form of a signal level are then plotted on the polar diagram of the horizontal plane, and the sound can be heard through the loudspeaker. Furthermore, the results of this study can be used for the development of a RDF independently, and its implementation in the passive radar.